High-heat-resistance polyimide enameled wire and preparation method thereof

By using cetyl trimethylammonium bromide modified ZrO2 powder in polyimide enameled wire, the problem of insufficient heat resistance in high temperature environments is solved, higher thermal decomposition temperature and tensile strength are achieved, flame retardant performance is enhanced, and application scenarios are expanded.

CN119517492AActive Publication Date: 2025-02-25SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411716666.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing polyimide enameled wires are insufficient in high temperature environments and cannot meet the stricter requirements for use in high temperature environments.

Method used

ZrO2 powder modified with cetyl trimethylammonium bromide was added as an additive to the polyimide insulating paint, and the tensile strength and heat resistance of the enameled wire insulating paint layer were improved through specific treatment.

Benefits of technology

The thermal decomposition temperature and tensile strength of the enameled wire insulating paint layer are significantly improved, reaching a thermal decomposition temperature of 520℃ and a tensile strength of 88MPa, while enhancing the flame retardant performance and expanding the application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517492A_ABST
    Figure CN119517492A_ABST
Patent Text Reader

Abstract

The invention discloses a high-heat-resistance polyimide enameled wire and a preparation method thereof. The high-heat-resistance polyimide enameled wire comprises a copper or aluminum wire and a polyimide insulating paint layer arranged on the wire, and the insulating paint layer is formed by immersing the wire into a polyamide acid solution containing cetyltrimethylammonium bromide modified ZrO2 powder for coating, and carrying out multi-stage heating treatment and heating curing. The CTAB modified zirconium oxide is used, and the CTAB modified ZrO2 powder is added for the first time to prepare the insulating paint layer of the polyimide enameled wire, so that the tensile strength and the heat resistance of the insulating paint layer in the enameled wire are effectively improved, the thermal decomposition temperature of the polyimide insulating paint layer can be increased to 520 DEG C, and the tensile strength can be increased to 88 MPa; and meanwhile, the insulating and flame-retardant properties of the enameled wire are improved, and the application scene of the polyimide enameled wire is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of enameled wires, and in particular to a high-heat-resistant polyimide enameled wire and a preparation method thereof. Background Art

[0002] Enameled wire is a type of winding wire, which consists of a metal wire and an insulating varnish coated on its surface. It is usually prepared by coating, where the varnish is coated on the surface of the wire and then dried and solidified. Enameled wire is widely used in motors and electrical appliances, and the quality of the insulating varnish of the enameled wire directly affects the operation and life of the electrical equipment. With the continued rapid growth of the electric power industry and the rapid development of household appliances, the miniaturization, lightweight and high power of parts are important trends in the development of electrical products. Small size and high power will cause the coil to generate a lot of heat during operation. At the same time, during the operation of the motor, the winding is energized and rotates continuously. Long-term power supply and friction will generate a lot of heat, which puts higher requirements on the temperature resistance level of the enameled wire. The temperature resistance of the enameled wire is mainly affected by the insulating varnish.

[0003] At present, the main materials of insulating paint for enameled wires are concentrated in polyester, polyurethane and polyester imide. Among them, polyimide is a special engineering plastic with excellent performance. Its main chain contains an imide structure. It performs well in heat resistance, solvent resistance and extreme environment resistance. It is one of the organic polymer materials with the best comprehensive performance. It has been widely used in insulating paint. Enameled wires using polyimide insulating paint have the advantages of high heat resistance, refrigerant resistance, low dielectric loss, good insulation performance, severe cold resistance, radiation resistance, high mechanical strength, stable electrical performance, chemical resistance, and strong overload capacity. Although polyimide enameled wires are the enameled wires with the highest heat resistance grade, their long-term use temperature can reach more than 220°C, but they still cannot meet the current more stringent high temperature environment requirements. Therefore, it is necessary to develop polyimide insulating paints with higher heat resistance. The commonly used methods at present include adding silicon oxide, aluminum oxide, graphene inorganic reinforcing materials, adjusting polymer monomers or polymer polymerization structures, etc. There are many studies on adding non-polar reinforcing materials to improve heat resistance. For example, CN112592653A discloses a method for preparing a high-temperature resistant polyimide wire enamel, which uses surface-modified graphene oxide and a polyimide system to compound. Graphene oxide has an ultra-high specific surface area and a two-dimensional planar nanostructure, and has the possibility of being compounded with a polyimide system to obtain heat resistance and high mechanical properties. CN115746696A discloses a high-heat-resistant polyimide enameled wire, which uses a polyamic acid solution obtained by in-situ polycondensation of aromatic dianhydride, aromatic diamine and fluorinated amino graphene as a polyimide varnish, and thus prepares an enameled wire. The obtained enameled wire has excellent mechanical, high-temperature durability and low dielectric loss properties while maintaining excellent heat resistance. CN111154100A discloses a method for preparing a highly heat-resistant polyimide, wherein γ-aminopropyltriethoxysilane is used as a raw material to prepare a cage-shaped octapoly (γ-aminopropyl) silsesquioxane, and then a modified polyimide is prepared using raw materials such as cage-shaped octapoly (γ-aminopropyl) silsesquioxane, diamine, and dianhydride. The unique cage structure of the cage-shaped octapoly (γ-aminopropyl) silsesquioxane has excellent mechanical properties and thermodynamic stability. When it is introduced into the synthetic raw materials of the polyimide precursor, the comprehensive mechanical properties of the polyimide can be improved, and the elastic properties and heat resistance of the polyimide can be improved. CN109535713A discloses a hollow microsphere / polyimide composite material, including hollow microspheres and a polyimide resin matrix, wherein the hollow microspheres are uniformly dispersed in the polyimide resin matrix; the composite material has the characteristics of high heat resistance, excellent mechanical properties, and stable broadband low dielectric properties. However, there are still the following defects. First, the addition of a large amount of powder will affect the performance of polyimide. Second, after the introduction of inorganic powder, there will be dispersion problems in the polyimide precursor, and agglomeration may occur, resulting in limited performance improvement of polyimide insulating varnish.In order to improve the dispersion effect, inorganic oxide particles are currently pretreated with coupling agents or surfactants. However, the cost of coupling agent-modified oxide particles is high, which will increase the manufacturing cost of the product. At the same time, the introduction of coupling agents will introduce more impurities into the product, affecting the performance of the product. If the coupling agent is removed by heat treatment, it is likely to introduce more pores into the oxide, affecting the long-term stability and durability of the product. Long-term use may lead to reduced product performance and shortened life. There are also studies on adjusting the organic composition or polymer structure of insulating varnish to improve its heat resistance. For example, CN115472332A discloses an enameled wire, in which the conductor is sequentially covered with a first varnish layer, a second varnish layer, and a third varnish layer; it selects a suitable insulating varnish, and through the adjustment of process parameters, the performance of each varnish layer is fully utilized to obtain an enameled wire with high heat resistance, which greatly improves the heat resistance of the product and meets the use requirements of oil-cooled drive motors of high-voltage platforms above 800V. CN104073155A discloses a polyimide wire enamel, which selects different dianhydrides to prepare different polyamic acid solutions, and the different polyamic acid solutions are blended in proportion as required to form a paint solution, which improves the heat resistance temperature and greatly increases the elongation at break, increases the toughness, and is not easy to break during winding.

[0004] Although the polyimide insulating varnish currently obtained already has good heat resistance, with the emergence of complex operating environments such as high power and high voltage, polyimide enameled wires with higher temperature resistance levels are still required, which is also an important direction for the development of the industry. Summary of the invention

[0005] The present invention aims to overcome the problems in the prior art and provide a high heat-resistant polyimide enameled wire, which has higher heat resistance while meeting the mechanical properties and weather resistance of conventional polyimide enameled wires, can further improve its high-temperature service life and expand its application field.

[0006] To achieve the above-mentioned purpose of the present invention, the first aspect of the present invention provides a high heat-resistant polyimide enameled wire, which includes a conductor and a polyimide insulating varnish layer arranged on the conductor, wherein the polyimide insulating varnish layer is formed by heating and curing a polyamic acid solution containing hexadecyltrimethylammonium bromide-modified ZrO2 powder. The applicant unexpectedly discovered through a large number of experiments that the addition of hexadecyltrimethylammonium bromide-modified ZrO2 powder to the polyimide insulating varnish can effectively improve the tensile strength and heat resistance of the insulating varnish layer in the enameled wire. Compared with the polyimide insulating varnish layer directly adding zirconium oxide powder, the insulating varnish layer of the specific additive used in the present invention has a thermal decomposition temperature of 520°C and a tensile strength of 88MPa, which is relatively higher than the decomposition temperature of 495°C and the tensile strength of 51MPa of ZrO2 directly added without modification, further expanding the application scenarios of polyimide enameled wire.

[0007] As a preferred technical solution, the conductor is a copper wire or an aluminum wire, and the thickness of the polyimide insulating paint layer is 0.01-0.1 mm.

[0008] As an optimal technical solution, the preparation method of the hexadecyltrimethylammonium bromide modified ZrO2 powder is as follows: 10-20g ZrOCl2·8H2O solid is dissolved in distilled water to obtain a zirconium oxychloride solution with a concentration of 0.5-1mol / L; 1% of the solid mass of ZrOCl2·8H2O is weighed and dissolved in distilled water to obtain a CTAB solution with a concentration of 0.01-0.05mol / L; the CTAB solution is slowly added dropwise to the zirconium oxychloride solution under stirring until it is uniformly mixed; the uniformly mixed solution is transferred to a hydrothermal kettle, reacted at 140-180°C for 6-12 hours, centrifuged and washed to collect the precipitate, and placed in an oven at 50-90°C for 3-9 hours to obtain the hexadecyltrimethylammonium bromide modified ZrO2 powder.

[0009] As a preferred technical solution, the method for preparing the polyamic acid solution comprises the following steps: 1) Weigh 0.99 mol to 1.01 mol of dibasic acid anhydride and dissolve it in 1 L of organic solvent, stir and continuously introduce protective gas to obtain solution A; 2) Weigh a certain amount of ZrO2 powder modified with hexadecyltrimethylammonium bromide, and slowly add it to solution A under stirring and continuous introduction of protective gas until it is evenly dispersed to obtain solution B; 3) Weigh 0.98 mol to 1 mol of diamine and dissolve it in solution B. Stir and continuously introduce protective gas. After it is evenly dispersed, react at 50-80°C for 4-12 hours and cool to room temperature to obtain the product.

[0010] As a preferred technical solution, the dibasic acid anhydride is at least one of pyromellitic acid anhydride, 3,3',4,4'-biphenyltetracarboxylic acid anhydride or 3,3',4,4'-benzophenonetetracarboxylic acid anhydride; the diamine is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine or 4,4'-diaminobenzophenone; and the organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0011] As a preferred technical solution, the protective gas is one of nitrogen, helium and argon, and the added amount of the hexadecyltrimethylammonium bromide-modified ZrO2 powder is 1% to 5% of the mass of the diamine.

[0012] Another aspect of the present invention provides a method for preparing a high heat-resistant polyimide enameled wire, comprising the following steps: 1) Preparation of hexadecyltrimethylammonium bromide modified ZrO2 powder: weigh and dissolve 10-20g ZrOCl2·8H2O solid in distilled water to obtain a zirconium oxychloride solution with a concentration of 0.5-1mol / L; weigh 1% of the solid mass of ZrOCl2·8H2O and dissolve it in distilled water to obtain a CTAB solution with a concentration of 0.01-0.05mol / L; slowly drop the CTAB solution into the zirconium oxychloride solution under stirring until it is uniformly mixed; transfer the uniformly mixed solution to a hydrothermal autoclave, react at 140-180°C for 6-12 h, collect the precipitate by centrifugation, wash, and place it in an oven at 50-90°C for 3-9 h to dry it and then take it out; 2) Preparation of polyamic acid solution: Weigh 0.99 mol to 1.01 mol of dibasic acid anhydride and dissolve it in 1L of organic solvent, stir and continuously introduce protective gas to obtain solution A; weigh a certain mass of ZrO2 powder modified by hexadecyltrimethylammonium bromide, slowly add it to solution A under stirring and continuous introduction of protective gas until it is evenly dispersed to obtain solution B; weigh 0.98 mol to 1 mol of diamine and dissolve it in solution B, stir and continuously introduce protective gas, react at 50-80°C for 4-12h after evenly dispersed, and cool to room temperature; 3) Immersing the conductor into the polyamic acid solution obtained in step 2) for coating, and performing a multi-stage heating treatment until the surface of the conductor is coated with a polyimide insulating paint layer of a desired thickness.

[0013] As a preferred technical solution, the conductor is a copper wire or an aluminum wire, and the thickness of the polyimide insulating paint layer is 0.01-0.1 mm.

[0014] As a preferred technical solution, the dibasic acid anhydride is at least one of pyromellitic acid anhydride, 3,3',4,4'-biphenyltetracarboxylic acid anhydride or 3,3',4,4'-benzophenonetetracarboxylic acid anhydride; the diamine is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine or 4,4'-diaminobenzophenone; the organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide, and the added amount of the hexadecyltrimethylammonium bromide-modified ZrO2 powder is 1% to 5% of the mass of the diamine.

[0015] As a preferred technical solution, the step 3) is specifically as follows: placing the polyamic acid solution into a fixed container of a pulling coating machine, immersing the wire at a speed of 40 to 60 mm / min, and then lifting it at a speed of 10 to 30 mm / min for coating. The coated wire is placed in a tubular furnace and sequentially kept at 70 to 90°C for 2 to 4 hours, 140 to 160°C for 40 to 60 minutes, 220 to 240°C for 30 minutes to 40 minutes, and 280 to 300°C for 30 minutes to 40 minutes.

[0016] The present invention also provides an application of high-heat-resistant polyimide enameled wire, which is wound into a winding coil for use in motor equipment. The motor equipment using the winding coil can achieve miniaturization and high power, and still has high stability under long-term high temperature conditions. At the same time, the introduction of CTAB-modified zirconium dioxide powder also improves the flame retardant properties of the polyimide insulating paint layer, further improving the safety of the enameled wire product.

[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: The present invention proposes for the first time to use ZrO2 powder modified with hexadecyltrimethylammonium bromide as an additive to prepare the insulating varnish layer of polyimide enameled wire. The CTAB-modified ZrO2 powder obtained by specific treatment is added to the polyimide insulating varnish to effectively improve the tensile strength and heat resistance of the insulating varnish layer in the enameled wire. Compared with the polyimide insulating varnish layer directly added with zirconium oxide powder, the thermal decomposition temperature of the insulating varnish layer of the present invention can reach 520°C, and the tensile strength also reaches 88MPa. At the same time, on the basis of improving the heat resistance stability, the flame retardant effect of the polyimide insulating layer is also enhanced, thereby expanding the application scenarios of the polyimide enameled wire.

[0018] At the same time, the enameled wire preparation method of the present invention has a simple process, and the CTAB-modified ZrO2 powder in the polyimide insulating varnish layer is dispersed and uniformly distributed, which effectively inhibits the insulating varnish delamination failure caused by sedimentation, agglomeration, etc. of conventional oxide powder in the polyamic acid solution, and greatly improves the heat resistance and mechanical strength of the polyimide enameled wire. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a cross-sectional SEM image of the enameled wire prepared in Comparative Example 1; Figure 2 The cross-sectional SEM and EDS spectra of the enameled wire prepared in Comparative Example 1 are shown; Figure 3 is a cross-sectional SEM image of the enameled wire prepared in Example 1; Figure 4 The cross-sectional SEM and EDS spectra of the enameled wire prepared in Example 1 are shown; Figure 5It is the FT-IR image of ZrO2 powder before and after CTAB modification; Figure 6 It is the TGA test graph of the enameled wire prepared in Example 1 and Comparative Example 1 and Comparative Example 2; Figure 7 It is a comparison chart of the dielectric constants of the enameled wires prepared in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0020] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0021] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0022] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0023] Example 1

[0024] A high heat-resistant polyimide enameled wire is prepared by the following method: 1) Preparation of hexadecyltrimethylammonium bromide modified ZrO2 powder: weigh and dissolve 10g ZrOCl2·8H2O solid in distilled water to obtain a zirconium oxychloride solution with a concentration of 0.5mol / L; weigh 0.1g hexadecyltrimethylammonium bromide and dissolve it in distilled water to obtain a CTAB solution with a concentration of 0.01mol / L; slowly drop the CTAB solution into the zirconium oxychloride solution under stirring until it is uniformly mixed; transfer the uniformly mixed solution to a hydrothermal autoclave, react at 140℃ for 6h, collect the precipitate by centrifugation, wash, and place it in an oven at 50℃ for 3h to dry it and then take it out to obtain CTAB-ZrO2; 2) Preparation of polyamic acid solution: Weigh 0.99 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride and dissolve it in 1 L of N,N-dimethylformamide, stir and continuously introduce nitrogen to obtain solution A; weigh 1.96 g of CTAB-ZrO2 powder and slowly add it to solution A under stirring and continuous nitrogen conditions until it is evenly dispersed to obtain solution B; weigh 0.98 mol of 4,4'-diaminodiphenyl ether and dissolve it in solution B, stir and continuously introduce nitrogen, react at 50°C for 4 hours after it is evenly dispersed, and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pulling coating machine, immerse the copper wire at a speed of 40mm / min, and then lift it at a speed of 10mm / min for coating. Put the coated copper wire into the tubular furnace and keep it at 70℃ for 2h, 140℃ for 40min, 220℃ for 30min, and 280℃ for 30min in sequence, until the surface of the wire is covered with a 0.01mm polyimide insulating paint layer.

[0025] The thermal decomposition temperature of the enameled wire at a weight loss rate of 10% was measured to be 520°C, the tensile strength was 88MPa, and the dielectric constant was 2.6 at 200KHz.

[0026] Example 2

[0027] A high heat-resistant polyimide enameled wire is prepared by the following method: 1) Preparation of hexadecyltrimethylammonium bromide modified ZrO2 powder: weigh and dissolve 20g ZrOCl2·8H2O solid in distilled water to obtain a zirconium oxychloride solution with a concentration of 1 mol / L; weigh 0.2g hexadecyltrimethylammonium bromide and dissolve it in distilled water to obtain a CTAB solution with a concentration of 0.05 mol / L; slowly drop the CTAB solution into the zirconium oxychloride solution under stirring until it is uniformly mixed; transfer the uniformly mixed solution to a hydrothermal autoclave, react at 180°C for 12 h, collect the precipitate by centrifugation, wash, and place it in an oven at 90°C for 9 h to dry it, and then take it out to obtain CTAB-ZrO2; 2) Preparation of polyamic acid solution: 1.01 mol of pyromellitic anhydride was weighed and dissolved in 1 L of N-methylpyrrolidone, stirred and continuously introduced argon to obtain solution A; 9.81 g of CTAB-ZrO2 powder was weighed and slowly added to solution A under stirring and continuous argon conditions until it was evenly dispersed to obtain solution B; 0.98 mol of 4,4'-diaminodiphenyl ether was weighed and dissolved in solution B, stirred and continuously introduced argon, and after uniform dispersion, the mixture was reacted at 80°C for 12 hours and cooled to room temperature; 3) Put the polyamic acid solution into the fixed container of the pulling coating machine, immerse the copper wire at a speed of 60 mm / min, and then lift it at a speed of 30 mm / min for coating. Put the coated copper wire into the tubular furnace and keep it at 90℃ for 4h, 160℃ for 60min, 240℃ for 40min, and 300℃ for 40min in sequence, until the surface of the wire is covered with a 0.1mm polyimide insulating paint layer.

[0028] The thermal decomposition temperature of the enameled wire at a weight loss rate of 10% was measured to be 523°C, the tensile strength was 82MPa, and the dielectric constant was 3.2 at 200KHz.

[0029] Example 3

[0030] A high heat-resistant polyimide enameled wire is prepared by the following method: 1) Preparation of hexadecyltrimethylammonium bromide modified ZrO2 powder: weigh and dissolve 20g ZrOCl2·8H2O solid in distilled water to obtain a zirconium oxychloride solution with a concentration of 1 mol / L; weigh 0.2g hexadecyltrimethylammonium bromide and dissolve it in distilled water to obtain a CTAB solution with a concentration of 0.05 mol / L; slowly drop the CTAB solution into the zirconium oxychloride solution under stirring until it is uniformly mixed; transfer the uniformly mixed solution to a hydrothermal autoclave, react at 150°C for 8 h, collect the precipitate by centrifugation, wash, and place it in an oven at 70°C for 4 h to dry it and then take it out to obtain CTAB-ZrO2; 2) Preparation of polyamic acid solution: Weigh 1.0 mol of pyromellitic anhydride and dissolve it in 1 L of N-methylpyrrolidone, stir and continuously introduce argon to obtain solution A; weigh 6.37 g of CTAB-ZrO2 powder and slowly add it to solution A under stirring and continuous argon conditions until it is evenly dispersed to obtain solution B; weigh 1 mol of 4,4'-diaminobenzophenone and dissolve it in solution B, stir and continuously introduce argon, react at 60°C for 5 hours after it is evenly dispersed, and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pulling coating machine, immerse the copper wire at a speed of 50 mm / min, and then lift it at a speed of 10 mm / min for coating. Put the coated copper wire into the tubular furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 30min, and 300℃ for 30min in sequence, until the surface of the wire is covered with a 0.05mm polyimide insulating paint layer.

[0031] The thermal decomposition temperature of the enameled wire at a weight loss rate of 10% was measured to be 521°C, the tensile strength was 84MPa, and the dielectric constant was 2.9 at 200KHz.

[0032] Comparative Example 1 A polyimide enameled wire is prepared by the following method: 1) Preparation of ZrO2 powder: weigh and dissolve 20 g of ZrOCl2·8H2O solid in distilled water to obtain a zirconium oxychloride solution with a concentration of 1 mol / L; slowly add an ammonia solution with a pH value of 12 to the zirconium oxychloride solution under stirring until the pH value is 10 to obtain a white precipitate; wash the white precipitate three times with anhydrous ethanol to remove impurities to obtain a zirconium hydroxide precipitate; put the zirconium hydroxide precipitate into a hydrothermal reactor with a filling ratio of 60%, react at 200°C for 4 hours, wash the obtained product alternately with deionized water and anhydrous ethanol, then centrifuge it in a centrifuge at 9000 r / min for 6 times, and finally place it in a drying oven at 80°C for 38 hours to obtain zirconium dioxide powder; 2) Preparation of polyamic acid solution: Weigh 1.0 mol of pyromellitic anhydride and dissolve it in 1 L of N-methylpyrrolidone, stir and continuously introduce argon to obtain solution A; weigh 6.37 g of ZrO2 powder and slowly add it to solution A under stirring and continuous argon conditions until it is evenly dispersed to obtain solution B; weigh 1 mol of 4,4'-diaminobenzophenone and dissolve it in solution B, stir and continuously introduce argon, react at 60°C for 5 hours after it is evenly dispersed, and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pulling coating machine, immerse the copper wire at a speed of 50 mm / min, and then lift it at a speed of 10 mm / min for coating. Put the coated copper wire into the tubular furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 30min, and 300℃ for 30min in sequence, until the surface of the wire is covered with a 0.05mm polyimide insulating paint layer.

[0033] The thermal decomposition temperature of the enameled wire at a weight loss rate of 10% was measured to be 495°C, the tensile strength was 51MPa, and the dielectric constant was 1.9 at 200KHz.

[0034] Comparative Example 2 A polyimide enameled wire is prepared by the following method: 1) Preparation of polyamic acid solution: 1.0 mol of pyromellitic anhydride was weighed and dissolved in 1 L of N-methylpyrrolidone, stirred and continuously introduced argon gas to obtain solution A; 1 mol of 4,4'-diaminobenzophenone was weighed and dissolved in solution A, stirred and continuously introduced argon gas, dispersed evenly, reacted at 60°C for 5 hours, and cooled to room temperature; 2) Put the polyamic acid solution into the fixed container of the pulling coating machine, immerse the copper wire at a speed of 50 mm / min, and then lift it at a speed of 10 mm / min for coating. Put the coated copper wire into the tubular furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 30min, and 300℃ for 30min in sequence, until the surface of the wire is covered with a 0.05mm polyimide insulating paint layer.

[0035] The thermal decomposition temperature of the enameled wire at a weight loss rate of 10% was measured to be 479°C, the tensile strength was 49.8MPa, and the dielectric constant was 1.5 at 200KHz.

[0036] Comparative Example 3 A polyimide enameled wire is prepared by the following method: 1) preparing zirconium oxide powder according to the method in Comparative Example 1; 2) First, take 55 mL of distilled water and adjust its pH value to 5 with glacial acetic acid, then add 150 mg of silane coupling agent KH-550, stir at room temperature until hydrolyzed, and obtain a coupling agent solution; according to the mass ratio of zirconium dioxide powder to coupling agent of 100:3, take zirconium dioxide powder and add it to the coupling agent solution, stir mechanically at a speed of 600 r / min for 35 minutes, then place it in a constant temperature drying oven at 120°C for 45 minutes, and finally grind it with a mortar to obtain modified zirconium dioxide powder; 3) Preparation of polyamic acid solution: Weigh 1.0 mol of pyromellitic anhydride and dissolve it in 1 L of N-methylpyrrolidone, stir and continuously introduce argon to obtain solution A; weigh 6.37 g of modified ZrO2 powder and slowly add it to solution A under stirring and continuous argon conditions until it is evenly dispersed to obtain solution B; weigh 1 mol of 4,4'-diaminobenzophenone and dissolve it in solution B, stir and continuously introduce argon, react at 60°C for 5 hours after it is evenly dispersed, and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pulling coating machine, immerse the copper wire at a speed of 50 mm / min, and then lift it at a speed of 10 mm / min for coating. Put the coated copper wire into the tubular furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 30min, and 300℃ for 30min in sequence, until the surface of the wire is covered with a 0.05mm polyimide insulating paint layer.

[0037] The thermal decomposition temperature of the enameled wire at a weight loss rate of 10% was measured to be 484°C, the tensile strength was 57MPa, and the dielectric constant was 1.6 at 200KHz.

[0038] The enameled wires prepared in Example 1 and Comparative Example 1 were subjected to cross-sectional scanning and energy spectrum analysis. The results are shown in Figure 1~Figure 4The cross-sectional scanning image of Example 1 shows no obvious agglomerated granular objects, and the CTAB-ZrO2 particles are evenly dispersed in the insulating paint layer, indicating that the CTAB-modified nanoparticles have a smaller particle size and can be better dispersed in the PI matrix. The cross-sectional scanning image of Comparative Example 1 shows some obvious agglomerated large granular objects attached to the cross-sectional surface.

[0039] from Figure 5 The FT-IR infrared spectra of ZrO2 powder before and after CTAB modification show that the -1 The broad vibration band centered at 503 and 615 cm-1 is the absorption peak of the OH bond in the H2O molecule. -1 The absorption bands at 1357~1386 cm are due to the existence of Zr-O-Zr bonds, confirming the formation of ZrO2 nanostructures. -1 The weak absorption peak centered at 1454 cm is related to the vibration of COH. From the FT-IR spectrum, the ZrO2 nanopowder sample has a stronger absorption band than the CTAB-modified ZrO2 sample due to its larger grain size. -1 There is a CH bending vibration in the CTAB molecule nearby, indicating that ZrO2 has been successfully modified.

[0040] Figure 6 The thermal weight loss test diagram of the enameled wire prepared in Example 1 and Comparative Examples 1 and 2 shows that the thermal decomposition temperatures of the pure PI film, PI / ZrO2 composite film and PI / CTAB-ZrO2 composite film at a weight loss rate of 10% are 479.4°C, 494.7°C and 520°C respectively. The ZrO2 modified by CTAB significantly improves the high temperature resistance of the PI film and the heat resistance of the enameled wire. The improvement in heat resistance may be due to the fact that the positively charged groups carried by CTAB can significantly reduce the surface tension of the particles, effectively prevent the agglomeration of the particles, improve the interface bonding between the filler and the polymer matrix, and improve the application of the PI composite film in high temperature environments.

[0041] Figure 7 The following is a curve showing the change of the dielectric constant of the enameled wires prepared in Example 1, Comparative Example 1 and Comparative Example 2 from low frequency to high frequency at 25°C and 1 MHz. At a frequency of 200 KHz, the dielectric constants of pure PI, PI / ZrO2 and PI / CTAB-ZrO2 composite layers are 1.5, 1.9 and 2.6, respectively, and in a higher frequency range, the dielectric constant of the PI / CTAB-ZrO2 insulating varnish layer remains at a relatively high value, thereby improving the dielectric stability of the composite film.

[0042] The above is a detailed introduction to a high heat-resistant polyimide enameled wire and its preparation method. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.

Claims

1. A high heat-resistant polyimide enameled wire, comprising a conductor and a polyimide insulating varnish layer arranged on the conductor, characterized in that: The polyimide insulating varnish layer is formed by heating and curing a polyamic acid solution containing hexadecyltrimethylammonium bromide-modified ZrO2 powder.

2. The high heat-resistant polyimide enameled wire according to claim 1, characterized in that: The conductor is a copper wire or an aluminum wire, and the thickness of the polyimide insulating paint layer is 0.01-0.1 mm.

3. The high heat-resistant polyimide enameled wire according to claim 1, characterized in that: The preparation method of the hexadecyltrimethylammonium bromide modified ZrO2 powder is as follows: 10-20g ZrOCl2·8H2O solid is dissolved in distilled water to obtain a zirconium oxychloride solution with a concentration of 0.5-1mol / L; 1% of the solid mass of ZrOCl2·8H2O is weighed and dissolved in distilled water to obtain a CTAB solution with a concentration of 0.01-0.05mol / L; the CTAB solution is slowly added dropwise to the zirconium oxychloride solution under stirring conditions until it is uniformly mixed; the uniformly mixed solution is transferred to a hydrothermal kettle, reacted at 140-180°C for 6-12h, centrifuged and washed to collect the precipitate, and placed in an oven at 50-90°C for 3-9h to obtain the hexadecyltrimethylammonium bromide modified ZrO2 powder.

4. The high heat-resistant polyimide enameled wire according to claim 1, characterized in that: The polyamic acid solution is prepared by the following method: Step 1: Weigh 0.99 mol to 1.01 mol of dibasic acid anhydride and dissolve it in 1 L of organic solvent, stir and continuously introduce protective gas to obtain solution A; Step 2: Weigh the ZrO2 powder modified with hexadecyltrimethylammonium bromide, and slowly add it to solution A under stirring and continuous introduction of protective gas until it is evenly dispersed to obtain solution B; Step 3: Weigh 0.98 mol to 1 mol of diamine and dissolve it in solution B. Stir and continuously introduce protective gas. After it is evenly dispersed, react at 50-80°C for 4-12 hours and cool to room temperature to obtain the product.

5. The high heat-resistant polyimide enameled wire according to claim 4, characterized in that: The dibasic acid anhydride is at least one of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride; the diamine is at least one of 4,4'-diaminodiphenyl ether and 4,4'-diaminobenzophenone; and the organic solvent is at least one of N,N-dimethylformamide and N-methylpyrrolidone.

6. The high heat-resistant polyimide enameled wire according to claim 4, characterized in that: The protective gas is one of nitrogen and argon, and the added amount of the ZrO2 powder modified by hexadecyltrimethylammonium bromide is 1% to 5% of the mass of the diamine.

7. A method for preparing the high heat-resistant polyimide enameled wire according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: Prepare hexadecyltrimethylammonium bromide modified ZrO2 powder: weigh and dissolve 10-20g ZrOCl2·8H2O solid in distilled water to obtain a zirconium oxychloride solution with a concentration of 0.5-1mol / L; weigh 1% of the solid mass of ZrOCl2·8H2O and dissolve it in distilled water to obtain a CTAB solution with a concentration of 0.01-0.05mol / L; slowly drop the CTAB solution into the zirconium oxychloride solution under stirring until it is uniformly mixed; transfer the uniformly mixed solution to a hydrothermal autoclave, react at 140-180°C for 6-12h, collect the precipitate by centrifugation, wash and collect it, place it in an oven at 50-90°C for 3-9h and then take it out; Step 2: Prepare a polyamic acid solution: weigh 0.99 mol to 1.01 mol of a dibasic acid anhydride and dissolve it in 1 L of an organic solvent, stir and continuously introduce a protective gas to obtain a solution A; weigh ZrO2 powder modified with hexadecyltrimethylammonium bromide, slowly add it to solution A while stirring and continuously introducing a protective gas until it is uniformly dispersed to obtain a solution B; weigh 0.98 mol to 1 mol of a diamine and dissolve it in solution B, stir and continuously introduce a protective gas, and after uniform dispersion, react at 50 to 80°C for 4 to 12 hours, and cool to room temperature; Step 3: Immerse the wire in the polyamic acid solution obtained in step 2 for coating, and perform multi-stage heating treatment until the surface of the wire is coated with a polyimide insulating paint layer of a desired thickness.

8. The method for preparing high heat-resistant polyimide enameled wire according to claim 7, characterized in that: The conductor is a copper wire or an aluminum wire, and the thickness of the polyimide insulating paint layer is 0.01-0.1 mm.

9. The method for preparing a high heat-resistant polyimide enameled wire according to claim 7, characterized in that: The dibasic acid anhydride is at least one of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride; the diamine is at least one of 4,4'-diaminodiphenyl ether and 4,4'-diaminobenzophenone; the organic solvent is selected from at least one of N,N-dimethylformamide and N-methylpyrrolidone, the added amount of the hexadecyltrimethylammonium bromide modified ZrO2 powder is 1% to 5% of the mass of the diamine, and the protective gas is one of nitrogen and argon.

10. The method for preparing high heat-resistant polyimide enameled wire according to claim 7, characterized in that: The step 3 is specifically as follows: putting the polyamic acid solution into a fixed container of the pulling coating machine, immersing the wire at a speed of 40 to 60 mm / min, and then lifting it at a speed of 10 to 30 mm / min for coating, putting the coated wire into a tubular furnace, and sequentially keeping it at 70 to 90° C. for 2 to 4 hours, keeping it at 140 to 160° C. for 40 to 60 minutes, keeping it at 220 to 240° C. for 30 minutes to 40 minutes, and keeping it at 280 to 300° C. for 30 minutes to 40 minutes.

Citation Information

Patent Citations

  • Preparation method of nano zirconium dioxide powder

    CN104324685A

  • Method for synthesizing thermostable lamellar nanocrystalline zirconia

    CN106629843A

  • Preparation method for self-cleaning anti-corrosive coating on magnesium alloy surface

    CN107556865A

  • Preparation method of zirconium dioxide modified polyimide composite material enameled wire

    CN116218358A

  • Thermally stable monolith catalyst for reforming reaction

    US20180030357A1

Cited By

  • Insulating layer for electromagnetic wire and preparation process thereof

    CN120748857A